Odpowiedzi

2009-12-15T17:08:51+01:00
Z pierwszego x-y= 0 dowiadujesz się że x=y więc y pomijamy i mamy
2x+z=4
3x+3z=9

2x=4-z
x=2-1/2z
podstawiamy do 2 równania i mamy 3(2-1/2z)+3z=9
6-3/2z+3z=9
3/2z= 3
z=2
podstaw do 1 2x+2=4
2x=2
x=1
sprawdzenie
2+2=4
3+6=9
Najlepsza Odpowiedź!
2009-12-15T17:12:41+01:00
(x-y=0
(x+y+z=4
(x+2y+3z=9

(x=0+y
(x+y+z=4
(x+2y+3z=9

(x=y
(x+x+z=4 |- 2x
(x + 2x +3z =9

(x=y
(z=4-2x
(x + 2x +3 (4-2x) =9

(x=y
(z=4-2x
(3x + 12 - 6x =9| - 12

(x=y
(z=4-2x
(-3 x = -3 | / (-3)

(x=y
(z=4-2x
(x = 1

(1=y
(z=4 - 2
(x = 1

x = 1
y = 1
z = 2